Benzyl Dihydrazone versus Thiosemicarbazone Schiff Base: Effects on the Supramolecular Arrangement of Cobalt Thiocyanate Complexes and the Generation of CoN6 and CoN4S2 Coordination Spheres. Issue 40 (24th October 2017) - Mahmoudi, Ghodrat; Zaręba, Jan K.; Gurbanov, Atash V.; Bauzá, Antonio; Zubkov, Fedor I.; Kubicki, Maciej; Stilinović, Vladimir; Kinzhybalo, Vasyl; Frontera, Antonio
Abstract : In this study, we examine the coordination chemistry of benzyl dihydrazone and thiosemicarbazone Schiff bases featuring different chelation modes, steric bulk, and reactivities towards cobalt(II) thiocyanate. The tetradentate benzyl dihydrazone ligands coordinate to the Co(SCN)2 fragment to form CoN6 coordination spheres (1–3 ), whereas the thiosemicarbazone ligands provide Co III complexes featuring CoN4 S2 coordination spheres (4 and5 ) and charge‐balancing anions SCN – and [Co(SCN)4 ] 2– for4 and5, respectively. Hirshfeld surface (HS) analysis revealed a substituent effect that results in an increasing number of H··· H contacts in the order –H < –CH3 < –Ph (1 –3, respectively). The H bonding in4 and5 as well as the associated energies were computed by the DFT approach, and these interactions appear to be crucial for the formation of the supramolecular systems. The DFT study also suggested that the H‐bonded dimers in5 are examples of the recently described "antielectrostatic" H bonds. Abstract : We explore the coordination chemistry of benzyl dihydrazone and thiosemicarbazone Schiff bases featuring different chelation modes, steric bulks, and reactivities towards Co(SCN)2 . Trends in the supramolecular arrangement are explored through Hirshfeld surface analysis and DFT calculations. The DFT results indicate that the H‐bonded dimers in5 are "antielectrostatic" H bonds.